Prasiolin, a new UV-sunscreen compound in the terrestrial green macroalga Prasiola calophylla (Carmichael ex Greville) Kützing (Trebouxiophyceae, Chlorophyta) - Hartmann, Anja (Planta, 2015)
We introduced a novel combination of chromatographic techniques for the purification and analysis of a new UV-sunscreen mycosporine-like amino acid (MAA) in the terrestrial green algaPrasiola calophylla. Prasiola calophylla (Carmichael ex Greville) Kützing (Trebouxiophyceae, Chlorophyta) is a typical member of terrestrial algal communities in temperate Europe, where it regularly experiences various stress conditions including strong diurnal and seasonal fluctuations in ultraviolet radiation (UVR). As a photoprotective mechanism Prasiola species and other related Trebouxiophycean taxa synthesize a mycosporine-like amino acid (MAA) as natural sunscreen whose chemical structure was unknown so far. In the present study a new methodological approach is described for the isolation, purification and structural elucidation of this novel sunscreen in P. calophylla. The new compound exhibits an absorption maximum at 324 nm (in the short ultraviolet-A), a molecular weight of 333 and a molecular extinction coefficient of 12.393 M(−1) cm(−1), and could be identified as N-[5,6 hydroxy-5(hydroxymethyl)-2-methoxy-3-oxo-1-cycohexen-1-yl] glutamic acid using one- and two-dimensional (1)H and (13)C-NMR spectroscopy. As trivial name for this novel MAA we suggest ‘prasiolin’. The ecologically essential function of prasiolin for UVR-protection in terrestrial algae of the Trebouxiophyceae is discussed.